2014
DOI: 10.1177/0300060514530879
|View full text |Cite
|
Sign up to set email alerts
|

Henoch–Schönlein purpura in 535 Chinese children: clinical features and risk factors for renal involvement

Abstract: Objectives: To analyse the clinical features of Henoch-Schönlein purpura (HSP) with or without nephritis in Chinese children and to determine the risk factors for renal involvement. Methods: Patient characteristics, clinical parameters and laboratory data were retrospectively analysed in patients with HSP with or without nephritis. Logistic regression analysis was used to identify the risk factors for renal involvement. Results: A total of 535 patients with HSP were included in the study. HSP nephritis occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
1
31
2
4
Order By: Relevance
“…Although GIS involvement is mentioned as a risk factor for renal involvement in many previous studies, 7,8,10,17,30,35,37 we could not demonstrate any association. Purpura on sites other than the lower limbs 33,35 and scrotal involvement 7,9 were also described as risk factors, which we could not define. In the meta-analysis, scrotal involvement was not found to be associated with renal involvement, either.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Although GIS involvement is mentioned as a risk factor for renal involvement in many previous studies, 7,8,10,17,30,35,37 we could not demonstrate any association. Purpura on sites other than the lower limbs 33,35 and scrotal involvement 7,9 were also described as risk factors, which we could not define. In the meta-analysis, scrotal involvement was not found to be associated with renal involvement, either.…”
Section: Discussioncontrasting
confidence: 88%
“…Although some studies showed a positive correlation between CRP values and renal involvement, 7,8 some others including the most recent meta-analysis found no correlation. 10,35,37 We could not demonstrate any other association with other laboratory parameters in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Tablo 2' de farklı çalışmalarda bulunmuş kötü prognoz risk faktörleri yer almaktadır 5,6,12,14,[17][18][19] . Genel olarak; yaşın büyük olması, döküntünün atipik yerleşimli olması, döküntünün 1 aydan uzun süre devam etmesi ve belirgin GİS tutulumu olması çoğu çalışmada risk faktörleri arasında yer almıştır.…”
Section: Discussionunclassified
“…Dados demográficos, clínicos, laboratoriais e tratamento em 296 pacientes com e sem nefrite da púrpura de Henoch-Schönlein (NPHS) nos primeiros 3 meses após o diagnóstico presente estudo evidenciou NPHS em cerca de metade dos pacientes nos primeiros 3 meses após o diagnóstico, sendo associada especialmente com púrpura persistente e sangramento GI. Aproximadamente um terço dos -se no fato de ser um estudo de desenho retrospectivo com possível perda de dados, e a ausência de análise da IgA1 sérica deficiente em galactose, que hoje tem sido considerada um marcador prognóstico da PHS27 .A prevalência da NPHS no início da doença foi similar a outros estudos, nos quais variou de 20 a 80%5,17,28,29 . A maioria dos pacientes apresentou alterações renais leves, enquanto que síndrome nefrótica e IRA foram raramente observadas no início desta vasculite primária, como previamente reportado30 .…”
unclassified